The Factors Influencing the Career Choices of Western students and International Students: The Role of Culture - Zhou, Xin (Journal of Theory and Practice of Contemporary Education, 2023)
Positive career choices bring university students a sense of fulfilment in life, but they are impacted by culture. However, most existing research has neglected the issue of career choice among international students, particularly from a comparative, cross-cultural perspective. Accordingly, this work analyses the existing literature on the career choices of Western students and international students using an extended literature review method and a three- dimensional framework including intrinsic, extrinsic and interpersonal factors. A total of 47 pieces of literature are included in the review and the findings suggest that international students focus more on combining personal interests and social responsibility, occupational social prestige and family/social obligations in their career choices than Western students. Furthermore, culture only influences students' career choices to a certain extent. Further research should explore the relationship between extrinsic factors and the career choices of international students, with a particular focus on the impact of the pandemic. Consequently, this study can help universities and educators deepen their understanding of students' career choices from a cultural perspective and thus help prepare students to become more productive members of the workforce.